Expression of O6-Alkylguanine-DNA Alkyltransferase in Normal and Malignant Bladder Tissue of Egyptian Patients - Abir A. Saad; Heba Sh. Kassem; Andrew C. Povey; Geoffrey P. Margison (Journal of Nucleic Acids)
Bladder tumour tissues and corresponding uninvolved mucosa (normal tissue) of Egyptian bladder cancer patients were assessed for O6-alkylguanine-DNA-alkyltransferase (MGMT) activity by functional assay of tissue extracts (36 paired samples), and distribution by immunofluorescence (IF) microscopy of fixed material (24 paired samples). MGMT varied widely from 42–253 fmoles/mg protein and from 3.2–40 fmoles/μg DNA in normal and 58–468 fmoles/mg protein and 2.5–49.5 fmoles/mg protein, in the tumour tissues; only one tumour had undetectable activity. Pairwise comparison of MGMT activity in tumour and adjacent normal tissue showed no significant difference based on DNA content but was 1.75-fold higher in tumour (P<.01) based on protein. There was no effect of gender or bilharzia infection status. IF showed that in tumours, both the mean percentage of positive nuclei (57.3 ± 20.3%) and mean integrated IF (5.47 ± 3.66) were significantly higher than those in uninvolved tissues (42.8 ± 13.5%   P=.04) and (1.89 ± 1.42; P<.01), respectively. These observations suggest that, overall, MGMT levels are increased during human bladder carcinogenesis and that MGMT downregulation is not a common feature of bladder cancers. Based on this, bladder cancers would be expected to be relatively resistant to chemotherapy which involved O6-guanine alkylating antitumour agents.